KEPEMIMPINAN DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM - Muhammad Alfiannur; Yahya Mof; Dina Hermina (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
Leadership in the management of Islamic educational institutions plays a very important role in creating an educational system that is effective, high quality and oriented towards Islamic values. This article aims to examine the concept of leadership in the context of Islamic educational institutions, including relevant leadership models, the challenges faced, and their impact on educational management. Using a qualitative approach and literature study, this research found that leadership based on Islamic principles such as trust, justice, and deliberation can strengthen the governance of educational institutions, improve the quality of learning, and create a conducive environment for the development of student character. However, challenges such as limited human resources, funds and social change are the main obstacles that require adaptive and visionary leadership. This research concludes that good leadership in the management of Islamic educational institutions can produce quality education that is relevant to the needs of the times